Malaysian teachers’ views on robot-mediated intervention to train autism spectrum disorder (ASD) children on emotional regulation - Abdul Alim Sidique, Faizanah; Abd Karim, Aishah Hanim; Khalid, Madihah; Abd Hamid, Siti Rafiah; Badzis, Mastura; Sidek, Shahrul Na'im; Md Yusof, Hazlina; Dzulkarnain, Ahmad Aidil Arafat; Rashidan, Mohammad Ariff (University of Malaya, 2024)
This qualitative study explored the views of teachers and an occupational therapist about the potential use of humanoid robots as an assistive tool in educating autism spectrum disorder (ASD) children. Seven participants with extensive experience handling early intervention programs for ASD children were selected via purposive sampling. Semi-structured interviews and focus group discussion (FGD) were applied as data collection method. Data gained were analyzed using thematic analysis. Four main themes were identified from the study, they are: (1) Teachers’ knowledge about robots, (2) Robots increase children's engagement, (3) Roles of robots in intervention, and (4) advantages and disadvantages of using robots. All participants had observed a robot-mediated intervention involving interactions between ASD children and a humanoid robot. It was observed that most of the children at the center liked interacting with the robot, suggesting that the use of robots could benefit ASD children. However, these interactions must be monitored and limited to a certain period to avoid over-dependence on robot use. This study provides a novel perspective on robotics and a practical example of how to use robots to enhance learning outcomes for ASD children.